PELAKSANAAN PENDAFTARAN HAK ATAS TANAH SECARA SISTEMATIK MELALUI PROYEK AJUDIKASI DI SAMARINDA - Anggi Elfia Risky Putri (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe registration of land rights through the Adjudication project in Samarinda, in practice is not complicated and the registration is easy. Where the location has been determined based on the criteria in the decision of the Minister of Agrarian Affairs no. 3 of 1995 where the location of the evidence is still small or the land has not been registered by the owner. Land registration through this adjudication is more effective than sporadic land registration by the landowners themselves. For in Samarinda The registration of land through the adjudication project has reached the target of 10,000 fields because in Samarinda from land registration through the project Adjudication according to Government Regulation No.24 of 1997 and Article 19 UUPA has been reached that is the legal certainty of each with the existence of certificate as evidence. In the implementation of registration through this adjudication project can not be separated from the factors that support the cheap registration fee is only Rp. 13,500,00 and the registrant does not need to pursue administrative care, and the registration requirements are easy, so this implementation is easier to implement. However, there are also factors that hamper the government, which includes short time, the presence of problematic soil, lack of complete data on the land to be registered, and the government in providing counseling must be repeatedly. While the inhibiting factor of the community as the land owner includes the required data has not been attached, the parcel number does not match the transferred number, or also the deletion in the certificate is not executed, filling the application letter of incomplete rights, and the silence if there is a mistake the data has been collected by the Adjudication Team so that this will affect the implementation of registration of land rights through adjudication projects. With the factors that hinder the findings of efforts to overcome them, such as by increasing the registration time and not only targeted 5,000 field 1 team, and provide counseling to land owners to complete the land data, and to resolve the land dispute (if the dispute), also held unfit data correction where the land owner actively checks the land data that has been announced by the Adjudication Team. Thus the factors hindering the implementation of the registration of land rights systematically through adjudication projects can be overcome so that the implementation runs smoothly in accordance with the objective of Government Regulation No.24 of 1997 on the need for land registration.